Toxicity of organic UV-filters to the aquatic midge Chironomus riparius - Campos, Diana; Gravato, Carlos; Quintaneiro, Carla; Golovko, Oksana; Žlábek, Vladimír; Soares, Amadeu M V M; Pestana, João L T (Ecotoxicology and environmental safety, 2017)
Despite the frequent detection of organic ultraviolet-filters (UV-filters) in freshwater sediments, there is a lack of ecotoxicological data undermining a correct risk assessment for these emerging contaminants. The present study assessed the effects of three of the most commonly used UV-filters (benzophenone-3 - BP3; 3-(4-methylbenzylidene)camphor - 4-MBC and octocrylene - OC) on Chironomus riparius life history and biochemical responses. Standard ecotoxicological assays confirmed that all compounds impaired growth of C. riparius larvae and induced developmental effects such as delayed emergence and a reduction of imagoes weight. Concerning the biochemical responses analysed no evidences of oxidative damage in lipids or neurotoxicity (tested assessing acetylcholinesterase activity) were observed for any of the tested compounds. However, 4-MBC exposure induced a decrease in catalase activity and an increase in glutathione-S-transferase activity at 14.13mg/Kg while OC exposure caused an increase in total glutathione levels at 0.23 and 18.23mg/Kg. Exposure to all UV-filters tested, increased energy consumption on C. riparius with significant differences above 1.00mg/Kg for BP3, 0.09mg/Kg for 4-MBC and 2.13mg/Kg for OC. These results suggest that environmental relevant concentrations of UV-filters can cause deleterious effects to aquatic benthic species, such as C. riparius, and call for further research concerning effects of organic UV-filters on natural invertebrate communities and ecosystem functioning.
Keywords: Acrylates; Catalase; Glutathione Transferase; zvířata; ženské pohlaví; larva; katalasa; Camphor; Larva; Acetylcholinesterase; Biomarkers; Water Pollutants, Chemical; Benzophenones; Aquatic macroinvertebrates; Female; mužské pohlaví; benzofenony; glutathiontransferasa; akryláty; Sublethal effects; kafr; chemické látky znečišťující vodu; Personal care products; Sunscreening Agents; Animals; Male; přípravky chránící proti slunci; acetylcholinesterasa; Chironomidae